Commodification of Local Culture In Cigarette Commercials: Semiotic Analysis On Dji Sam Soe Commercial “Mahakarya Indonesia 2016” - Emmanuel Putro Prakoso (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Being restricted directly displaying cigarettes on commercials forces cigarette manufacturers and creative teams to work hard to create a cigarette commercial that can attract consumers’ attention. This is the reason why many cigarette manufacturers show scenes laden with local culture elements in their commercials as an effort to bring their products closer to the consumers. Local culture-themed commercials beginning to bloom on the television aim not only to preserve Indonesian local cultural values but also to protect them from being claimed by other countries. This research aims to get an overview of an alleged exploitation of Sumbawa local culture in Dji Sam Soe cigarette commercial Mahakarya Indonesia 2016 version. The research method used here is semiotic analysis with approaches from Roland Barthes, which are linguistics and connotative and denotative iconic message. Several vital scenes indicate practices of exploitation of Sumbawa local culture in the advertisement. These practices of local culture exploitation are marked by the emergence of scenes where Sumbawa people work together to build boats and houses (denotation), a long-time characteristic of Indonesian society, along with verbal and written message (linguistics) shown through the back sound of a man saying,“From the youths to the elders, to the youths.”and “One Nusantara collaborate to create an effort in which equal burden is bore on the shoulders!”.These sentences send both denotative and connotative messages that are important to be analyzed further.